ANTIBACTERIAL ACTIVITY OF OIL EXTRACT OF TRIGONA PROPOLIS - Pujirahayu, Niken; Ritonga, Halimahtussaddiyah; L, Satya Agustina; Uslinawaty, Zakiah (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: This research is aimed to determine antibacterial activity of some solvents of raw propolis extracts of Trigona sp from Sulawesi, Indonesia and compare it with antibacterial activities of ethanolic and aqueous extracts. Methods: Propolis samples were extracted with water, ethanol, propylene glycol, olive oil, and Virgin Coconut Oil (VCO). An agar-well diffusion assay was used to evaluate the antimicrobial potential of propolis against Escherichia coli, Salmonella thypi, and Staphylococcus aureus. Results: The oily extract of propolis showed a potent antibacterial activity compared to the ethanol extracts against Staphylococcus aureus and Esherichia coli. Inhibition zone of Olive Oil Extracts of Propolis on S. aureus was higher (22.4 mm) than Ethanolic extracts and Water Extracts. Inhibition zone of Virgin Coconut Oil (VCO) propolis extract and Olive oil extract on E. coli were 9.5 mm and 9.3 mm, respectively. The oily extracts also showed higher action against E. coli compared with the ethanol extracts and propylene extracts. Conclusion: The propolis extracts obtained with Virgin Coconut Oil (VCO) and olive oil as solvent have higher antibacterial activity than the ethanolic extracts. So the VCO and Olive Oil can be used to extract raw propolis. Â